Annulation of O-silyl N,O-ketene acetals with alkynes for the synthesis of dihydropyridinones and its application in concise total synthesis of phenanthroindolizidine alkaloids - Lee, Seokwoo; Shin, Jae Eui; Yoon, Ran; Yoo, Hanbin; Kim, Sanghee (Frontiers in Chemistry, 2023)
The formation of N-heterocycles with multiple substituents is important in organic synthesis. Herein, we report a novel method for the construction of functionalized dihydropyridinone rings through the annulation of an amide α-carbon with a tethered alkyne moiety. The reaction of the amide with the alkyne was achieved via O-silyl N,O-ketene acetal formation and silver-mediated addition. Furthermore, the developed method was applied for the total synthesis of phenanthroindolizidine and phenanthroquinolizidine alkaloids. By varying the coupling partners, a concise and collective total synthesis of these alkaloids was achieved.